2016
DOI: 10.1055/s-0036-1582241
|View full text |Cite
|
Sign up to set email alerts
|

Venous Malformation and Localized Intravascular Coagulopathy in Children

Abstract: Localized intravascular coagulopathy (LIC) has been described in adults with venous malformation (VM) but rarely reported in children. This study aims to determine the prevalence of LIC in children with VM and associated risk factors. Patients younger than 18 years with VM from 2010 to 2014 were reviewed. Diagnosis was confirmed by Doppler ultrasound and/or magnetic resonance imaging. Demographics data and VM characteristics including volume, site, extension, painful symptoms, and palpable phleboliths were stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…About one-third of pediatric VMF patients are affected by localized intravascular coagulation and have D-dimer levels greater than 500 ng/mL. 9 Lesion size, presence of phleboliths, truncal location, and spongiform morphology on MRI were correlated with localized intravascular coagulation. 10 As shown in Fig 2 , laser plus sclerotherapy was accompanied in our patient by normalization of localized intravascular coagulation.…”
Section: Discussionmentioning
confidence: 97%
“…About one-third of pediatric VMF patients are affected by localized intravascular coagulation and have D-dimer levels greater than 500 ng/mL. 9 Lesion size, presence of phleboliths, truncal location, and spongiform morphology on MRI were correlated with localized intravascular coagulation. 10 As shown in Fig 2 , laser plus sclerotherapy was accompanied in our patient by normalization of localized intravascular coagulation.…”
Section: Discussionmentioning
confidence: 97%
“…It has also been indicated that notable sclerosing agent reflux causes serious complications. The effective rate of absolute ethanol treatment for low draining venous malformations has been reported as 75–95% (14,15,20); however, the efficacy of interventional therapy for Puig's classified advanced venous malformations has been unsatisfactory, which was reported to be at only 41% (21). To the best of our knowledge, this is the first study to report the use of absolute ethanol combined with n-butyl cyanoacrylate sclerotherapy in patients for the treatment of Puig's classified advanced venous malformation.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the series, 33%-88% of patients have some degree of d-dimer elevation and approximately 5% with decreased fibrinogen levels. [14][15][16][17] The detection of LIC and coagulopathy is important for 3 reasons. First, painful flareups may be associated with aggravation of those hematologic parameters associated with LIC and therefore conservative (eg, compression garments) or medical treatment directed to this portion of the coagulation cascade, that is, low molecular-weight heparin (LMWH) or direct anti-Xa agents may control and improve patient symptoms.…”
Section: Addressing Critical Preprocedures Hematologic Concernsmentioning
confidence: 99%
“…12,14,[18][19][20][21] Second, patients with coagulopathy are more likely to develop painful phleboliths, thrombophlebitis, deep venous thrombosis, and pulmonary embolism and therefore must be identified to allow appropriate thromboprophylaxis. 15,17 Third, and most importantly to the interventional radiologist, minor sclerotherapy among other factors can cause LIC to rapidly progress onto disseminated intravascular coagulation (DIC) either intra-or postprocedurally with life-threatening consequences. 13 The interventional radiologist must ensure patients are screened for risk of LIC and sent for appropriate lab studies, and where appropriate, be treated medically both periprocedurally and/or chronically.…”
Section: Addressing Critical Preprocedures Hematologic Concernsmentioning
confidence: 99%